The WTO Investment Facilitation for Development Agreement needs a strong provision on responsible business conduct - Karl P. Sauvant; Federico Ortino (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
The authors argue that a WTO Investment Facilitation for Development Agreement needs a strong responsible business conduct provision, as such a provision helps to increase the contribution that FDI can make to sustainable development. They suggest some elements of such a provision.
Keywords: 330